2016
DOI: 10.1128/mcb.00920-15
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Impairment Induces Recovery of Mitochondrial Membrane Potential and an Alternative Pathway of Mitochondrial Fusion

Abstract: Mitochondria are vital and highly dynamic organelles that continuously fuse and divide to maintain mitochondrial quality. Mitochondrial dysfunction impairs cellular integrity and is known to be associated with various human diseases. However, the mechanism by which the quality of mitochondria is maintained remains largely unexplored. Here we show that impaired proteasome function recovers the growth of yeast cells lacking Fzo1, a pivotal protein for mitochondrial fusion. Decreased proteasome activity increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…The molecular function of Mix23 in the IMS and the reasons that this factor is up-regulated during mitoprotein-induced stress remain unclear. An Rpn4-dependent regulation was also described before for Mia40 (33,66,67). Still, we found no indication that Mix23 is of relevance for the functionality of the mitochondrial disulfide relay in the IMS, and the deletion of MIX23 did not lead to synthetic defects in mia40-3 mutants.…”
Section: Discussionsupporting
confidence: 60%
“…The molecular function of Mix23 in the IMS and the reasons that this factor is up-regulated during mitoprotein-induced stress remain unclear. An Rpn4-dependent regulation was also described before for Mia40 (33,66,67). Still, we found no indication that Mix23 is of relevance for the functionality of the mitochondrial disulfide relay in the IMS, and the deletion of MIX23 did not lead to synthetic defects in mia40-3 mutants.…”
Section: Discussionsupporting
confidence: 60%
“…The mitochondrial membrane potential (ΔΨm) is an independent indicator of mitochondrial quality, responsible for basic functions of the mitochondria, such as protein import and synthesis in addition to ATP generation [ 27 , 28 ]. The sustained depolarization of mitochondria can induce apoptosis in target cells [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that mitochondrial function regulates 26S proteasome assembly and UPS regulates mitochondrial homeostasis (Alsayyah et al, 2020; Meul et al, 2020). Mitochondrial proteins in the outer and inner membranes and matrix are degraded by UPS following its ubiquitination, and UPS controls mitochondrial functions (Lavie et al, 2018; Lehmann et al, 2016; Liao et al, 2020; Shirozu et al, 2015). In addition, 3‐nitropropionic acid, which is known as an SDH inhibitor, influences the proteasome activity in Huntington's disease model cells (Hunter et al, 2007).…”
Section: Discussionmentioning
confidence: 99%